Soft Tissue Sarcoma of the Scalp Infiltrating the Occipital Bone: A Case Report - Ayoub Bakhil; Adam Benbachir; Amina Kahoul; Hicham Sabani; Lahcen Khalfi; Jalal Hamama; Karim El Khatib (Journal of Craniomaxillofacial Research)
Soft tissue sarcomas are rare, histologically heterogeneous malignant tumors. Head and neck localization accounts for 10% of cases, with a poor prognosis in the presence of infiltration of the skull bones or endocranial extension. Management remains essentially surgical plus or minus radiotherapy. We report the case of a young patient admitted for management of a large-volume atypical scalp sarcoma with infiltration of the occipital bone, necessitating surgical resection with cranioplasty.